2007
DOI: 10.1128/cvi.00081-07
|View full text |Cite
|
Sign up to set email alerts
|

Opsonophagocytic Activity and Other Serological Indications ofBordetella pertussisInfection in Military Recruits in Norway

Abstract: Bordetella pertussis is the causative agent of pertussis (whooping cough)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
15
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 45 publications
2
15
0
Order By: Relevance
“…This is one of a few studies that document increased vaccine- induced OPA against pertussis in human sera after revaccination with an acellular pertussis vaccine (19,36,40). In an earlier study, we found increased OPA in sera from military recruits who also had corresponding high levels of antibodies against pertussis (1). Those antibodies likely were reminiscent of previous infections rather than induced by vaccination, and the specificities of these antibodies probably were directed against a whole range of B. pertussis epitopes.…”
Section: Discussionmentioning
confidence: 49%
See 2 more Smart Citations
“…This is one of a few studies that document increased vaccine- induced OPA against pertussis in human sera after revaccination with an acellular pertussis vaccine (19,36,40). In an earlier study, we found increased OPA in sera from military recruits who also had corresponding high levels of antibodies against pertussis (1). Those antibodies likely were reminiscent of previous infections rather than induced by vaccination, and the specificities of these antibodies probably were directed against a whole range of B. pertussis epitopes.…”
Section: Discussionmentioning
confidence: 49%
“…OPA was measured as respiratory burst, as previously described (1). Briefly, live B. pertussis cells were used as target cells, and dihydrorhodamine 123 (Molecular Probes, Invitrogen)-primed polymorphonuclear neutrophils (PMNs) were used as effector cells.…”
Section: Bacterial Strainmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite the implementation of national programs for immunization against Bordetella pertussis (B. pertussis) and their acceptable vaccination coverage in many countries, this infection represents an important contribution to disease in different age subgroups, particularly in developing countries [1,2]. According to the reports of centers for disease control and prevention [3], B. pertussis remains the most commonly reported vaccine-preventable disease, especially in children.…”
Section: Introductionmentioning
confidence: 99%
“…Opsonophagocytosis assays were developed for a range of bacteria (24)(25)(26)(27) and have been widely used to assess immune responses to pneumococcal vac- antibody-mediated C3b/iC3b deposition levels in mother and cord samples separately against GBS serotypes Ia (mother, n ϭ 497; cord, n ϭ 478), Ib (mother, n ϭ 535; cord, n ϭ 521), II (mother, n ϭ 505; cord, n ϭ 499), III (mother, n ϭ 500; cord, n ϭ 483), and V (mother, n ϭ 518; cord, n ϭ 509). FI-C=, fluorescence index minus complement only.…”
Section: Discussionmentioning
confidence: 99%